Electronic Structure and Optical Properties of GaAs1-xBix Alloy - Xindong You; Renjie Zhou (Advances in Condensed Matter Physics)
A first-principles study has been performed to investigate the structural and electronic properties of the GaAs1-xBix system. The simulations are based upon the generalized gradient approximation (GGA) within the framework of density functional theory (DFT). Calculations are performed to different Bi concentrations. The lattice constant of GaAs1-xBix increases with Bi concentration while the alloy remains in the zinc-blende structure. The band gap of GaAs1-xBix clearly shrinks with the Bi concentration. The optical transition of Bi dopant in GaAs exhibits a red shift. Besides, other important optical constants, such as the dielectric function, reflectivity, refractive index, and loss function also change significantly.